Economic Efficiency of Ring Seiners Operated off Munambam Coast of Kerala Using Data Envelopment Analysis - V. Chandrasekar and Nikita Gopal
This paper has presented the economic efficiency, which includes technical as well as allocative efficiency, of ring seiners operating off the Munambam fishing harbour in Kerala. The model applied was the input- oriented Constant Return to Scale (CRS) Data Envelopment Analysis (DEA) with one output and six input variables. The analysis is based on a sample of 300 trips of 15 ring seine fishing vessels. The minimizing input-oriented CRS DEA results have indicated that the average technical efficiency and allocative efficiency of ring seiners operating off the Munambam coast is 53 per cent and 76 per cent, respectively. The overall economic efficiency of ring seiners has been found to be 40 per cent, ranging from 14.62 per cent to 100 per cent for individual DMUs (Decision Making Units). This study has found that the cost on fuel is highest (68%) in the total operational cost.